Plastic analysis of a laterally loaded pile shaft embedded in noncohesive soil - Kumar V.; Ghosh C. (My University, 2025)
Flexural behaviour of laterally loaded pile shaft in an elasto-plastic soil is considerably influenced by the type of variation of plastic resistance, soil modulus variation, and degree of fixity of the pile at the top. This paper presents a lower bound analysis of a laterally loaded single pile embedded in cohensionless material. For given lateral load at the tip of the pile and resulting soil pressure distribution along the length of pile, three cases have been studied. With increasing lateral loads, the moment carried by the pile will lead to the formation of plastic hinge at the location of maximum moment. Parametric results have been presented and charts have been prepared to find the length of the pile required for ultimate lateral load. The present approach is confined to the situation where lateral deflection of the pile is large.